The Villa’s Stratagem in Development of Agriculture- Based Tourism in Ubud, Bali - Kusuma Negara, I Made; Adikampana, I Made; Nugroho, Saptono (Udayana Journal of Social Sciences and Humanities; Vol 1 No 1 (2017): UJoSSH, Feburary 2017, 2017)
One of the favorite locations of villa in Ubud is the farm area that owned by local communities. It mentioned that the villa has consciously utilizing agricultural landscapes and their activities as a resource to attract tourists. But the existence of the villa has not been able to provide significant benefits for local communities, especially farmers. That can be observed by the emergence of resistance by farmers to the villa. This paper is addressed to the tactic or stratagem of villa in order to deal with of such resistance. The method is a qualitative approach. Data collected from observations and interviews with the villa management, local community representatives, and farmers. They were selected purposively, which they expected to provide comprehensive information about the villa and the local community. The data are grouped and then analyzed descriptively. The result of such analysis showed that the villa in maintaining its existence imposed some tactics or stratagems; the socio-cultural stratagem, economic stratagem, and political stratagem.